Amélie [videorecording (DVD)] - Jeunet, Jean-Pierre, 1953-; Tautou, Audrey, 1976-; Kassovitz, Mathieu, 1967- (Miramax Home Entertainment ; distributed by Buena Vista Home Entertainment, 2002)
Amélie is a young woman who had a decidedly unusual childhood; misdiagnosed with an unusual heart condition, Amélie didn't attend school with other children, but spent most of her time in her room, where she developed a keen imagination and an active fantasy life. Despite all this, Amélie has grown into a healthy and beautiful young woman who works in a cafe and has a whimsical, romantic nature. She decides to step into the lives of others around her to help them out.